All-round ionic liquids for shuttle-free zinc-iodine battery - Xiao, Tao (2024)
The practical implementation of aqueous zinc-iodine batteries (ZIBs) is hindered by the rampant Zn dendrites growth, parasite corrosion, and polyiodide shuttling. In this work, ionic liquid EMIM[OAc] is employed as an all-round solution to mitigate challenges on both the Zn anode and the iodine cathode side. First, the EMIM+ embedded lean-water inner Helmholtz plane (IHP) and inert solvation sheath modulated by OAc- effectively repels H2 O molecules away from the Zn anode surface. The preferential adsorption of EMIM+ on Zn metal facilitates uniform Zn nucleation via a steric hindrance effect. Second, EMIM+ can reduce the polyiodide shuttling by hindering the iodine dissolution and forming an EMIM+ -I3 - dominated phase. These effects holistically enhance the cycle life, which is manifested by both Zn || Zn symmetric cells and Zn-I2 full cells. ZIBs with EAc deliver a capacity decay rate of merely 0.01 ‰ per cycle after over 18,000 cycles at 4 A g-1 , and lower self-discharge and better calendar life than the ZIBs without ionic liquid EAc additive.